State, Nation, and the National Flag in Post-Soviet Lithuania: Legitimating Identities of the State in Institutional and Social Discourses. Issue 3 (18th June 2019) - Kesylytė-Alliks, Eglė
Abstract: This article explores discursive construction of legitimating identity(-ies) of the state within official institutional and semipublic social discourses on the national flag in post-1990 Lithuania. By doing so, it contributes to the continuous discussion regarding the puzzling coexistence of a relatively stable democratic regime and a limited degree of social and ethnic unrest with signs of political alienation in Lithuania. It argues that an empirical approach to legitimacy studies paired with research on national symbols and discourse analysis can contribute to a better understanding of this problem. The article concludes that the most prominent legitimating identity of the state coming forth in the official discourse is that of the state as an object of love and respect. This view is both shared and challenged within the semipublic discourse—especially regarding issues of instrumental performance of the state as well as the ability to accommodate both the initiative and autonomy of its people within political affairs.